FLEXIBILITY VERBA(L) PREFFIX ME- IN KUBU LANGUAGE IN JAMBI PROVINCE: STUDY OF THE STRUCTURE AND SEMANTIC - ristanto ristanto (Pusbindiklat - LIPI, 2015)
This study discusses flexibility verb(l) prefixes the Kubu language consisting of (1) the symptoms morphophonemic verb(l) prefixes me- in Kubu language, (2) categories which can join the verb(l) prefixes me-, and (3 ) grammatical meaning that is generated by of the prefix. The research use method descriptive. Methods of assessment in the form of distributional element techniques for direct, deletion, extension, substitution, and insertion. Data is taken from of their speaking and writing. This study took place in Sarolangun, Province of Jambi. The results of this study indicate that the categories that can be joined with the verb(l) prefixes me- in Kubu language is the form of (1) verb, (2) noun, (3) adjectives, and (4) numeral. Prefix me- is experiencing into a process morphophonemic meng-, m-, men-, mem-, meny-, and mong-. Grammatical meaning of the verb(l) prefixes me- in Kubu language are in the form of the ‘causative’ meaning and signifying ‘doing’.